Cardiovascular Remodeling Experienced by Real-World, Unsupervised, Young Novice Marathon Runners - D’Silva, Andrew; Bhuva, Anish N.; van Zalen, Jet; Bastiaenen, Rachel; Abdel-Gadir, Amna; Jones, Siana; Nadarajan, Niromila; Menacho Medina, Katia D.; Ye, Yang; Augusto, Joao; Treibel, Thomas A.; Rosmini, Stefania; et al. (Frontiers in Physiology, 2020)
Aims Marathon running is a popular ambition in modern societies inclusive of non-athletes. Previous studies have highlighted concerning transient myocardial dysfunction and biomarker release immediately after the race. Whether this method of increasing physical activity is beneficial or harmful remains a matter of debate. We examine in detail the real-world cardiovascular remodeling response following competition in a first marathon. Methods Sixty-eight novice marathon runners (36 men and 32 women) aged 30 ± 3 years were investigated 6 months before and 2 weeks after the 2016 London Marathon race in a prospective observational study. Evaluation included electrocardiography, cardiopulmonary exercise testing, echocardiography, and cardiovascular magnetic resonance imaging. Results After 17 weeks unsupervised marathon training, runners revealed a symmetrical, eccentric remodeling response with 3–5% increases in left and right ventricular cavity sizes, respectively. Blood pressure (BP) fell by 4/2 mmHg (P < 0.01) with reduction in arterial stiffness, despite only 11% demonstrating a clinically meaningful improvement in peak oxygen consumption with an overall non-significant 0.4 ml/min/kg increase in peak oxygen consumption (P = 0.14). Conclusion In the absence of supervised training, exercise-induced cardiovascular remodeling in real-world novice marathon runners is more modest than previously described and occurs even without improvement in cardiorespiratory fitness. The responses are similar in men and women, who experience a beneficial BP reduction and no evidence of myocardial fibrosis or persistent edema, when achieving average finishing times.